Mudharabah dan Musyarakah Sebagai Persepsi Keuangan Ekuitas Mikro Pelaku Usaha UMKM Wanita Kota Medan yang Kurang Beruntung - Alfi Amalia; Andrew Satria Lubis (Hikmah, 2022)
This study aims to determine the perceptions of disadvantaged women in the city of Medan regarding Sharia rules (Islamic law) on micro-equity financing instruments, mudharabah and musyarakah. This research was conducted through a survey method on 330 questionnaires on members of Islamic microfinance institutions (IsMFI), namely, the BMT Ar-Ridhwan sharia cooperative. The data obtained were analyzed using a structural equation model. The study results reveal that female BMT Ar-Ridhwan borrowers consider the sharia rules of mudharabah and musyarakah to require high moral and ethical values ​​and dynamic payment performance. They know several other basic provisions, such as liquidation of a business, transfer of shares, disclosure of information and termination of business. The overall findings of this study indicate that perceived Sharia rules are similar to those commonly used in general business partnerships between Muslims. It also shows that less fortunate entrepreneurs will accept rules that are easy to understand and benefit their interests. Furthermore, this indicates that the respondents' experience of microfinance and business operations does not significantly influence their perceptions of mudharabah and musyarakah instruments. The findings of this study can help IsMIF BMT Ar-Ridhwan take the initiative to offer mudharabah and musyarakah as micro-equity financing to economically disadvantaged women entrepreneurs.